Estudio del sistema automático de bombeo para agua potable utilizando como herramienta el software winpsp, para estructurar una propuesta de mejoramiento del proceso operativo en el edificio Alejandros ubicado en la ciudad de Quito 2015 - Herrera Yánez, Juan Carlos (2015)
This project aims to conduct a study in a pumping system for drinking water, structuring a proposal to improve the operating process of the system and take advantage of the operational capacity of the pumps and motors used; this will be done by using the software WINPSP from the pumps manufacturer DESMI, which is a Danish factory. The research methodology started from the hypothesis testing, demonstration of the problem, using the applicative following techniques: interviews and questionnaires to help us see the feasibility of the research project. The application site of this work is the "Alejandros" building located in the city of Quito, the investigative techniques were applied and the improvement proposal will be given to the building manager to put it into consideration for the owners to decide, whether to implement it or not....